Inflammatory Role of ROS-Sensitive AMP-Activated Protein Kinase in the Hypersensitivity of Lung Vagal C Fibers Induced by Intermittent Hypoxia in Rats - Yang, Chang-Huan; Shen, Yan-Jhih; Lai, Ching Jung; Kou, Yu Ru (Frontiers in Physiology, 2016)
Obstructive sleep apnea (OSA), manifested by airway exposure to intermittent hypoxia (IH), is associated with excess reactive oxygen species (ROS) production in airways, airway inflammation, and hyperreactive airway diseases. The cause-effect relationship for these events remains unclear. We investigated the inflammatory role of ROS-sensitive AMP-activated protein kinase (AMPK) in IH-induced airway hypersensitivity mediated by lung vagal C fibers (LVCFs) in rats. Conscious rats were exposed to room air (RA) or IH with or without treatment with N-acetyl-L-cysteine (NAC, an antioxidant), Compound C (an AMPK inhibitor), ibuprofen (a cyclooxygenase inhibitor), or their vehicles. Immediately after exposure, we found that intravenous capsaicin, phenylbiguanide, or α,β-methylene-ATP evoked augmented LVCF-mediated apneic responses and LVCF afferent responses in rats subjected to 24-h IH exposure in comparison with those in 24-h RA rats. The potentiating effect of IH on LVCF responses decreased at 6 h after and vanished at 12 h after the termination of IH exposure. The potentiating effect of IH on LVCF-mediated apneic and LVCF afferent responses was significantly attenuated by treatment with NAC, compound C, or ibuprofen, but not by their vehicles. Further biochemical analysis revealed that rats exposed to IH for 24 h displayed increased lung levels of lipid peroxidation (an index of oxidative stress), AMPK phosphorylation (an index of AMPK activation), and prostaglandin E2 (a cyclooxygenase metabolite), compared with those exposed to RA for 24 h. IH-induced increase in lipid peroxidation was considerably suppressed by treatment with NAC but not by compound C or ibuprofen. IH-induced increase in AMPK phosphorylation was totally abolished by NAC or compound C but not by ibuprofen. IH-induced increase in prostaglandin E2 was considerably prevented by any of these three inhibitor treatments. The vehicles of these inhibitors exerted no significant effect on the three IH-induced responses. These results suggest that 24-h IH exposure sensitizes LVCFs, leading to an exaggerated reflex and afferent responses to chemical stimulants in rats. Moreover, this IH-induced LVCF sensitization is mediated through a cascade of inflammatory responses in the airways involving increases in ROS, AMPK activation, and cyclooxygenase metabolite release.